A new arenicolous species of the genus Thyreophagus (Acari: Acaridae) from the Caspian sea coast: Taxonomy and ecological insights - Kolesnikov, Vasiliy B.; Klimov, Pavel B.; Khaustov, Alexander A.; Pepato, Almir; Makarova, Olga L. (Zootaxa, 2024)
A new sexual species, Thyreophagus subiasi sp. nov., inhabiting wet sands of the coastal zone of the Caspian Sea (Republic of Dagestan, Russia) is described. The new species is morphologically similar to Th. athiasae from Morocco (types redescribed here as well) but differs from it by the shape of the spermatheca and setae p and q on tarsi I–II represented by small triangular rudiments. As most other species of Thyreophagus inhabit subcortical habitats or stored food, Th. subiasi exhibits unusual ecology. We suggest that its elongated and flexible body may have facilitated adaptation to life in interstitial spaces among particles in coastal sandy environments. In this habitat, Th. subiasi co-occurred with long-bodied mesostigmatic mites from the genera Protogamasellus, Gamasellodes, and Neojordensia, suggesting that these mites are part of the coastal interstitial ecosystem.